First Isolation and Identification of Agriphages in Vegetable Crops in West Africa (Cȏte d’Ivorie): Potential Uses of Biocontrol in Plants - Akou Emmanuella Adioumani; Solange Kakou-Ngazoa; Noel David Trebissou Jonhson; Martin Thibaut; Addabah Audrey; Koudu Aristide; Sina K. Mireille; Aoussi Serge; Dosso Mireille (European Scientific Journal, ESJ, 2023)
Agriphages or bacterial viruses are ubiquitous in the environment. The discovery of virulent phages against phytobacteria improves crop growth and proposes biopesticide uses for plant diseases. In Africa, many phytobacteria such as Ralstonia, Clavibacter, and Xanthomonas were reported in several regions. This paper focuses on evaluating the presence of agriphages for the biocontrol of phytobacteria in Côte d'Ivoire. Leaves and soil samples were collected from healthy and diseased plants in three sites located in Anyama, Abidjan, and Bingerville. The pretreatments occurred with sterile and physiological water for leaves and soil samples, respectively. The isolation of agriphages was done on specific media with Xanthomonas campestris as bacterial host. Lytic activity was tested on agar media for five bacteria strains. After DNA extraction using the Qiagen method kit, molecular confirmation of agriphages was done by Random Amplified Polymorphic DNA-PCR. From this study, five (5) agriphages were isolated in soil and leaves in site 2. These agriphages have all been isolated from Xanthomonas campestris and have a broad spectrum of lytic activity. Molecular characterization by RAPD-PCR showed that three of these agriphages are DNA phages. The dendrogram showed that phages ΦXanS1 and ΦXanS2 have 93% similarities, while ΦXanS1 and ΦXanS2 are 62% similar to ΦXanF1. This study is the first reported agriphages in West Africa, alongside their potential uses against phytobacteria for biocontrol infection in crops.